Three essays on the role of credit, labor, and information for small business establishments - Gulati, Bhramman, author; Weiler, Stephan, advisor; Bernasek, Alexandra, advisor; Thilmany, Dawn, committee member; Vasudevan, Ramaa, committee member (Colorado State University. Libraries, 2024)
Small business establishments create jobs, promote innovation, and boost productivity in local and national economies. However, despite this pronounced and enduring impact, they face numerous existential challenges, especially in rural areas, which have smaller markets, population bases, and limited amenities compared to urban areas. Therefore, the United States government has introduced numerous policy measures to support and promote small establishments. This study informs such policy conversations by investigating three key factors that influence small business sustainability and growth: credit supply, labor supply, and information asymmetries. The first chapter reviews the study motivations and elaborates on these key factors. Existing literature outlines how lending from financial institutions plays an important role in the birth of new businesses. In Chapter 2, I add that bank lending fluctuations also impact the survival of existing (newborn) businesses, particularly in non-metropolitan areas. Next, Chapter 3 considers how local labor market dynamics affect the survival of new businesses by applying portfolio theory to evaluate employment-based and income-based measures of risk-and-reward trade-offs in local labor markets. I find that volatility in local labor markets observed during the study period, 2005-2009, has a positive impact on new business survival, especially in Metropolitan Statistical Areas. Thirdly, current and consistent information about a geographical entity's local economic, demographic, and social characteristics is a valuable commodity; however, such information is often scarce in rural and remote counties. The American Community Survey (ACS) was introduced to address this problem. However, its staggered data release—based on county population thresholds—created information gaps between otherwise similar rural counties. Therefore, Chapter 4 uses a synthetic control method to investigate any differences in economic impact between counties that received ACS information earlier and those that received it later (i.e., as measured through establishment births). There were encouraging results in some cases, indicating a potential economic effect from geographical information asymmetries. The last chapter reflects on the study's findings in the context of current economic events.
Keywords: economic resilience; labor economics; small business economics; information economics; business finance; regional economics